International Understandings of Health Literacy in Childhood and Adolescence—A Qualitative-Explorative Analysis of Global Expert Interviews - Schulenkorf, Tessa; Sørensen, Kristine; Okan, Orkan (International Journal of Environmental Research and Public Health)
(1) Background: With regard to children and adolescents, health literacy should only not be understood as an individual ability, but rather as dependent based on its contextual determinants. The study examines how experts define health literacy in childhood and adolescence and discusses whether they include these factors. (2) Methods: In 48 interviews with experts from 32 countries, specific questions for defining health literacy in childhood and adolescence were analyzed. Data analysis was conducted according to the summary of the qualitative content analysis. Main categories and subcategories were developed exploratively and inductively. (3) Results: No expert had an official definition of health literacy in childhood or adolescence. There were more experts who located health literacy only at the individual level alone than those who located it at both the individual and contextual levels. On the individual level, there was a focus on information processing, knowledge, behavior, and skills. At the contextual level, system responsibility, the ability of others, and relationship between age and development were the main points. (4) Conclusions: To develop an adequate method of dealing with health literacy in the target group, there must be a target group-specific consideration of the dependencies, ages, and developmental stages of that group. While this is considered as consensus in scientific discourse, it has seemingly not yet been adopted in development-related policies internationally.